The Frauds in Banking and Entrepreneurs by Electronic Devices and Combating Using Software and Employment of Demilitrized Zone in the Networks: Dr. Aftab Ahamd Malik, Dr. Mujtaba Asad, Dr. Waqar Azeem - Dr Aftab Ahmed Malik; Dr. Mujtaba Asad; Dr. Waqar Azeem (International Journal for Electronic Crime Investigation, 2022)
The malpractices and frauds are exponentially rising in developed and developing countries among entrepreneurs, banking as well as medium-sized companies. The criminals are utilizing the most modern information technology structures and such electronic media to accomplish their offense regarding fraud to cause wrongful loss and harm in the areas of white collar crimes, banking, business, and to individuals. The purpose of this research paper is to make these companies realize the essence of using the most recent, most reliable, and most authentic software and the need to make their networks more secure from outside attacks. The use of advanced features of tracking and hacking confidential information using information technology resources enables criminals to achieve their objectives. Basically, their modes of Operandi depend upon dishonesty and deception to complete the offense. In banking and white-collar frauds most of the time the employees of the concerned organizations are involved, who help and collaborate with external criminals by passing confidential information. Fraud is constituted by parody, distortion, misrepresentation, and twisting the fact/truth or concealment of real information detrimental to someone else. The legislation seems very naïve to punish a criminal who has committed fraud. There are several reasons for criminals to escape, for example, their identity most of the time remains hidden. Lack of evidence, feeble investigation, and naïve role of the prosecution in the court of law enable the criminals to go towards exoneration and release. The paper also presents an analysis of various types of fraud existing in society and how to combat them effectively. The main objective of fraudsters is to deprive people or entrepreneurs of their money, property, valuable documents, and private information. The authors of this paper express their deep concern about taking strict measures to safeguard the rights of bank customers by introducing the most recent software versions and the government must introduce stern and stringent legislation in this direction.